EPISTEMOLOGI TAFSIR NUSANTARA: Studi Atas Tafsir Fayd al-Rahman Karya K.H. Shaleh Darat - Didik Saepudin (Diya Al-Afkar: Jurnal Studi al-Quran dan al-Hadis, 2019)
K.H. Shaleh Darat was a 19th-century Javanese cleric who almost escaped the observation of the history of the Islamic archipelago. His concern for lay Muslims has made him have the courage to break the norm by translating and interpreting the Qur'an using the writings of pegon (Javanese-Arabic script). According to him, useful knowledge does not have to be in Arabic that seems "sacred". In addition, exoteric and esoteric interpretations (ishari) which direct Muslims to perform acts of virtue by only hoping for Allah as a form of teaching and earthing the values contained in the Qur'an, are certainly inseparable from socio-cultural influences and other sources on constructing his interpretation.